Feasibility Studies for Use of Copper Slag in Clinker Manufacture - Vanguri, Suresh; Palla, Suresh; Prasad, Gonthi; Chaturvedi, Sanjeev Kumar; Mohapatra, Bibekananda (UI Scholars Hub, 2022)
This study investigated the feasibility of using copper slag (CS-C) as a raw material in the production of Portland cement (PC). The effect of addition of 0%-3.5% CS-C on the clinkerization process, mineralogy, microstructure, and compressive strength development was studied. The Presence of CS-C in the raw mix resulted in the reduced temperature of clinkerization by about 50 °C. The quality of clinker prepared from the raw mix containing 3% CS-C and burned at 1400 °C was comparable to that of clinker prepared from the raw mix containing no CS-C and burned at 1450 °C. Gradual polymorphic modification of alite phase from rhombohedral to monoclinic upon the addition of CS-C was confirmed by X-ray diffraction (XRD) study. XRD and optical microscopy studies revealed the formation of more alite in the clinker prepared, at 1400 °C, from the raw mix containing 3% CS-C compared with the clinker prepared, at 1450 °C, from the raw mix containing no CS-C. This finding indicated the mineralizing effect of CS-C on clinkerization. Well-developed and large-sized alite grains were observed in the clinker samples prepared using CS-C. Portland clinker, prepared using CS-C as a raw mix component showed better mechanical performance characteristics than the control clinker. These results clearly establish the beneficial role of CS-C as a raw mix component in clinkerization and can replace conventional sources of iron such as laterite.